Mating structures for genomic selection breeding programs in aquaculture. Issue 1 (December 2016) - Sonesson, Anna; Ødegård, Jørgen
Abstract Background In traditional family-based aquaculture breeding, each sire is mated to two dams in order to separate the sire's genetic effect from other family effects. Factorial mating involves more mates per sire and/or dam and result in more but smaller full- and/or half-sib families. For traits measured on sibs of selection candidates, factorial mating increases intensity of selection between families when selection is on traditional best linear unbiased prediction (BLUP) estimated breeding values (TRAD -EBV ). However, selection on genome-wide estimated breeding values (GW -EBV ), uses both within- and between-family effects and the advantage of factorial mating is less obvious. Our aim was to compare by computer simulation the impact of various factorial mating strategies for truncation selection onTRAD -EBV versusGW -EBV on rates of inbreeding, accuracy of selection and genetic gain for two traits, i.e. one measured on selection candidates (CAND -TRAIT ) and one on their sibs (SIB -TRAIT ). Results Sire:dam mating ratios of 1:1, 2:2 or 10:10 were tested with 100, 200 or 1000 families produced from a constant number of parents (100 sires and 100 dams), and a mating ratio of 1:2 with 200 families produced from 100 sires and 200 dams. WithGW -EBV, changing the mating ratio from 1:1 to 10:10 had a limited effect on genetic gain (less than 5 %) for bothCAND -TRAIT andSIB -TRAIT, whereas withTRAD -EBV, selection intensity increased forSIB -TRAIT and genetic gain increased by 41 and 77 % for schemes with 3000 and 12, 000 selection candidates, respectively. For bothGW -EBV andTRAD -EBV, rates of inbreeding decreased by up to ~30 % when the mating ratio was changed from 1:1 to 10:10 for schemes with 3000 to 12, 000 selection candidates. Similar results were found for alternative heritabilities ofSIB -TRAIT and total number of tested sibs. Conclusions Changing the sire:dam mating ratio from 1:1 to 10:10 increased genetic gain substantially withTRAD -EBV, mainly through increased selection intensity for theSIB -TRAIT, whereas withGW -EBV, it had a limited effect on genetic gain for both traits. Rates of inbreeding decreased for both selection methods.